Determination of physicochemical quality of milk from dual purpose herds by unconventional tests in Colombia (Revista Sistemas de Producción Agroecológicos, 2014)
This work was performed in order to determine the physicochemical characteristics of milk (density, fat, acidity and pH) from dual purpose herds in the municipality of Villavicencio Meta, Colombia, through simple, practical and economical methods for establishing these parameters and can be handled by personnel with minimal training. Five farms were selected by choosing the cows were milked regardless which were in colostral period (less than 6 days postpartum), we proceeded to collect milk in buckets; then homogenized and subsequently filled in sterile containers which were identified and transported to the laboratory at the University of the Llanos under refrigeration for examination. Descriptive statistics were performed with the physicochemical variables, obtaining averages, standard deviation, standard error, variance, and maximum and minimum values. The density showed a high degree of reliability with the proposed method; the density compared between the determination with the thermolactodensimeter 15/15 versus unconventional showed high significance since the values ​​were similar variance equal number of observations and the mean minimum difference. Particle density is equal to that determined by the conventional method not less 0.004. The reliability was 79.8%, the proposed density method reliable under the environmental conditions of the study area. The fat test presented a high degree of reliability by analysis of variance regression, which two formulas for converting the result of the test unconventional fat percentage was generated conventional; also, data from the pH and alcoholometry test by regression analysis of variance were significant in high-grade (P>0.0001) to obtain the conversion formula for the test. conventional pH = 5.903 + 0.01023 (alcoholometry %). In the analysis of variance between the methods of acidity determined by titration with NaOH 0.1 N and the test proposed by alcoholometry the correlation coefficient between the two methods was low, which indicates that the test is not a reliable alcoholometry method for determining the acidity of milk.
Keywords: milk; fat; density; acidity